Are evaluated respiratory service developments implemented into clinical practice?. Issue 5 (18th September 2010) - Roberts, N J; Glasser, M; Partridge, M R
Abstract : Introduction: Evaluation of the way in which respiratory care is delivered is increasingly recognised to be an important area for research. When service developments are reported, it is not always clear whether they are subsequently implemented within the reporting institution, and if not why not. Methods: 3281 abstracts from three specialist journals and one general journal were reviewed, and 36 reported evaluated service developments identified. The authors of each of these were approached to determine whether the reported service developments were in use in their institution. Results: 30 of the 36 authors responded (83%). 10 reports were of sharing care with nurses and five with other health professionals, and the remainder involved new technologies, education, patient information or guideline implementation. 15/30 had implemented the reported development into practice, 11 of which were implemented immediately. Delays were due to staffing, funding and organisational issues. 10/15 studies were not put into practice, the main reason being that the key person had left. Four respondents embarked upon further study to confirm their preliminary published findings. Conclusions: Reports of apparently positive service developments are only implemented in approximately one-half of institutions reporting the development. In a third of cases, non-implementation reflects the original authors believing that further study is necessary to confirm effectiveness.